Kepuasan Konsumen Tidak Selalu Membentuk Loyalitas - Yasintha Soelasih (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
Train users in Indonesia began to increase, it can be seen from the data of passengers as a whole increased from year to year. These improvements must be supported with the customer perceived value, because it will affect of rail users. Long distance train in Indonesia distinguished its kind, namely the executive, business and economics. In this study, it more emphasis on the train executives, especially in Java. Issues examined here is whether the customer perceived value have an influence on satisfaction and commitment resulting in loyalty. This affects the sustainability of a rail business, because the level of competition arise among existing transportation, whether by air, land or sea. Sampling was done by simple random sampling, the number of respondents was 323. The instrument was tested with reliability and validity. The data used to answer the problem by using structural equation modeling with six hypotheses were tested. The results indicate that the hypothesis occurs between the customer perceived value influence consumer satisfaction and commitment. The effect between satisfaction and commitment to loyalty shows that satisfaction has no effect on loyalty, commitment while consumers have an influence on loyalty.